ANALYSIS OF THE ENFORCEMENT OF REGIONAL REGULATIONS ON PUBLIC ORDER, PEACE, AND COMMUNITY PROTECTION IN BANDUNG CITY - Annisa Rahmadanita; Agung Nurrahman (Jurnal Tatapamong, 2024)
Public order, peace, and community protection are under the responsibility of the Civil Service Police Unit (Satpol PP). The high prevalence of violations requires effective enforcement of the Regional Regulation on Public Order, Tranquility, and Community Protection. This research was conducted to analyze the implementation and enforcement of Bandung City Regional Regulation Number 9 of 2019 using a quasi-qualitative method with an inductive approach. Bandung City Government has established clear regulations regarding the matter. Unfortuantely, several challenges resulting from inadequate facilities and incentives for regional regulation enforcers persist, particularly for members of the sub-district Linmas and Linmas task forces at sub-district and city levels. This research shows that the implementation of relevant regulation by Satpol PP is categorized fairly good. Several aspects in the implementation can be further improved. Keywords: Regional Regulation, Law Enforcement, Public Order, Peace And Community Protection